Breaking Physiological Barriers in Women's Health: Mucoadhesive and Stimuli‐Responsive Nanomaterials - Maddox Parsons; Alivia R. Parker; Luke Schneider; Trisha Sullivan; Brittany E. Givens (WIREs Nanomedicine and Nanobiotechnology, 2026)
ABSTRACT Biomaterials are natural or synthetic molecules that exhibit biocompatibility, biodegradability, or bioresorbability. These materials are used for numerous health applications, including as drug delivery platforms. In drug delivery, biomaterials serve as drug carriers to enhance drug bioavailability and, consequently, treatment outcomes. Additionally, these biomaterial carriers may be functionalized to enhance targeting to a desired tissue. Specifically, in women's health, biomaterials may be designed to use the differences in pH, surface receptors, and cervicovaginal mucus in tissues such as the vagina, cervix, uterus, and ovaries to enhance local drug uptake. Recent advances in mucodiffusive drug delivery and stimuli‐responsive drug delivery are furthering the fields of drug delivery and women's health.